Effect of culture medium treated with non-thermal plasma energy othe growth and viability in-vitro of fibroblast cells from asian elephants (Elephas maximus) - Sarisa Klinhom (2020)
© 2019, Veteriner Fakultesi Dergisi. All rights reserved. Non-thermal plasma (NTP) is being developed for a wide-range of medical applications such as improvement of wound healing, elimination of infective microorganisms, and treatment of cancer. This study investigated the effect of culture medium exposed to NTP on the proliferation in-vitro of skin fibroblasts from Asian elephants. Dulbecco’s Modified Eagle’s Medium (DMEM) was used as culture medium and was exposed to NTP with three different intensities. The NTP reactive species Nitrite (NO2-) was measured in the treated medium before addition to cells. Fibroblasts were incubated for 24 h with NTP-treated complete medium supplemented with 10% Fetal Bovine Serum (FBS) and 1% antibiotic/antimycotic. Cell proliferation, the number of cells and viability rate were analysed using flow cytometry 24, 48 and 72 h after the start of the incubation. The proliferation rate of fibroblasts incubated with NTP treated medium was significantly higher (P<0.05) than controls and increased in a dose-dependent manner with increasing amount of NTP. Incubation of fibroblasts with NTP did not reduce their viability even at the highest dose of NTP. Culture medium treated with NTP energy may be used to improve healing of skin wounds in elephants. This study successfully shows that the medium treated with NTP was able to stimulate elephant skin fibroblasts proliferation and increase the total cell count but did not reduce cell viability in vitro. Containing buffering agent in culture media might reduce the effect of ROS generated by NTP. This might prevent using high dose of NTP to cause cell apoptosis and induce cell necrosis in this study. Future studies on the skin of living elephant are encouraged to develop more effective and optimum treatment conditions.